PENGARUH SUBSTITUSI TERIGU DENGAN TEPUNG KECAMBAH KACANG MERAH (Phaseolus vulgaris L) TERHADAP KARAKTERISTIK COOKIES - Nadya Citra Dewantari, I GAM.; Wisaniyasa, Ni Wayan; Suter, I Ketut (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2017)
This study aims to determine the effect of wheat flour substitution with red bean sprouts flour to cookies characteristics and to find out the exact concentration of red bean sprouts flour were produce the best cookies characteristics. This study used a completely randomized design with respectively wheat and red bean sprouts flour comparison (100% : 0%, 80% : 20%, 60% : 40%, 40% : 60%, 20% : 80%), the treatment was performed for three times thus obtained 15 experimental units. Data were analyzed by analysis of variance and if there was a treatment effect, then will be continue with Duncan test. The results showed that the treatment of red beans sprouts flour substitution effected on moisture content, ash content, protein content, fat content, fiber content, color, aroma, flavor, texture, and overall for cookies acceptance. Treatment was produced the best cookies characteristics were 40% wheat flour: 60% red bean sprouts flour, with characteristics were 3.27% moisture content, 2.29% ash content, 31.19% fat content, 7.26 % protein content, 55.96% carbohydrate content, 20.95% crude fiber content, light brown color (like), red beans typical aroma and liked, crunchy texture and liked, red beans typical flavor and liked, and overall acceptance and liked.
Keywords: wheat flour, red bean sprouts flour, characteristic, cookies